New Vaccine Technologies to Combat Outbreak Situations - Rauch, Susanne; Jasny, Edith; Schmidt, Kim E.; Petsch, Benjamin (Frontiers in Immunology, 2018)
Ever since the development of the first vaccine more than 200 years ago, vaccinations have greatly decreased the burden of infectious diseases worldwide, famously leading to the eradication of small pox and allowing the restriction or diseases such as polio, tetanus, diphtheria and measles. A multitude of research efforts focuses on the improvement of established and the discovery of new vaccines such as the HPV (human papilloma virus) vaccine in 2006. However, radical changes in the density, age distribution and travelling habits of the population worldwide as well as the changing climate favor the emergence of old and new pathogens that bear the risk of becoming pandemic threats. In recent years, the rapid spread of severe infections such as HIV, SARS , Ebola and Zika have highlighted the dire need for global preparedness for pandemics, which necessitates the extremely rapid development and comprehensive distribution of vaccines against potentially previously unknown pathogens. What is more, the emergence of antibiotic resistant bacteria calls for new approaches to prevent infections. Given these changes, established methods for the identification of new vaccine candidates are no longer sufficient to ensure global protection. Hence, new vaccine technologies able to achieve rapid development as well as large scale production are of pivotal importance. This review will discuss viral vector and nucleic acid-based vaccines (DNA and mRNA vaccines) as new approaches that might be able to tackle these challenges to global health.